Factors Affecting the First Childbearing Decision in Iranian Males - Marzieh Faghani Aghoozi; Nourossadat Kariman; Sanaz Faiazi; Mona Joze Mohtashami; Maliheh Amerian (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Childbearing results from a productive behavior within the family arisen from couples’ decision to have children. The role of men in making decisions about childbearing and their intentions are often overlooked in studies. Objective: This study aimed to investigate males’ first childbearing decision and their contributing factors. Materials and Methods: This was an analytical and cross-sectional study. In total, 300 married men aged 18-45 years participated in this study. The subjects accompanied their wives with the first pregnancy to receive prenatal care at hospitals and private health centers of Shahroud County, Iran. They were selected randomly. The required data were collected using A demographic form, Snyder’s Adult Hope Scale (AHS), and World Health Organization Quality of Life (WHOQOL-BREF) questionnaire. The correlation between study variables was examined by Pearson’s correlation coefficient and Multiple Linear Regression analysis. Results:  The mean age at first childbearing decision and age at marriage in men were 28.8±3.74 and 25.59±3.68 years, respectively. Among the factors related to first childbearing decision, age at marriage suggested the highest association (r=0.89, P=0.001). The age at first childbearing decision also had a statistically significant relationship with marriage duration (r=0.29, P=0.001), and education (r=0.16, P=0.001). Quality of life had a negative significant correlation with it (r=-0.22, P=0.001). Age at marriage revealed the highest power for predicting contributing factors. With the 10-year increase in men's marriage age, the age at first childbearing decision increased by 8.9 years; with the 1-point increase in quality of life score, the age decreased by 0.09 years, if other variables remained constant. Conclusion: Age at marriage and quality of life could affect age at first childbearing decisions in men. The healthcare team and policymakers should facilitate childbearing conditions. This could be achieved by providing accurate knowledge about these factors. As a result, men can achieve the desired number of children at the right time.